2009
DOI: 10.1177/112067210901900204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dose-Related Ocular Side Effects during Systemic Isotretinoin Administration

Abstract: During systemic isotretinoin treatment, eye dryness was related to the dose used, at least during the period of treatment. Conversely, the rate of conjunctival S aureus colonization was unrelated to the dose of isotretinoin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 17 publications
0
27
0
2
Order By: Relevance
“…Cumurcu et al (19) compared how the high-dose and low-dose isotretinoin treatments aff ect the vision. A group of 26 patients were treated with the high dose (> 0.5 mg kg -1 daily) of the drug and 25 patients with the low dose (< 0.5 mg kg -1 daily).…”
Section: Adverse Ocular Effectsmentioning
confidence: 99%
“…Cumurcu et al (19) compared how the high-dose and low-dose isotretinoin treatments aff ect the vision. A group of 26 patients were treated with the high dose (> 0.5 mg kg -1 daily) of the drug and 25 patients with the low dose (< 0.5 mg kg -1 daily).…”
Section: Adverse Ocular Effectsmentioning
confidence: 99%
“…All values of 10 seconds or less were considered abnormal. 10 Impression cytology samples were obtained with nitrocellulose acetate filter papers (Whatman; GE Healthcare UK Limited, Buckinghamshire, United Kingdom) pressed onto the superior temporal bulbar conjunctiva adjacent to the corneal limbus after application of topical anaesthesia. 11 Samples were kept in 95% ethanol at 4°C, stained with periodic acid-Schiff, and graded by a blinded operator according to the procedure by Nelson as grade 0, normal cytology; grade 1, early squamous metaplasia; and grades 2 and 3, increasing severity of metaplasia (Figs.…”
Section: Methodsmentioning
confidence: 99%
“…2 Cumurcu and colleagues further characterized the ophthalmic sequelae of isotretinoin and found that although patients on both low-and high-dose regimens reported photophobia, burning eyes, and ocular foreign body sensations, those in the high-dose group were more likely to exhibit these symptoms and were more bothered by them. 10 Patients in both groups reported that the adverse reactions resolved within 1 month of stopping isotretinoin treatment. Due to isotretinoin's drying effect, other patient-reported symptoms in these studies include pruritus, desquamation, epistaxis, dry nares, dry mucous membranes, dyspareunia, and abnormal menses.…”
Section: Common Minor Adverse Reactionsmentioning
confidence: 97%